Lost in Transition: The Dissemination of Digitization and the Challenges of Leading in the Military Educational Organization - Holth, Torill; Boe, Ole (Frontiers in Psychology, 2019)
This article aimed at studying how the Norwegian Ministry of Education and Research's intention of digitalization and specific primary goals of learning and teaching issued in 2017 could be retrieved in the overarching documents related to education in the Norwegian Armed Forces (NAF). A second aim was to investigate if digitalization and any digital tools were mentioned in the Norwegian Defence University College (NDUC) organization's study programs and subject plans for teaching, or if specific goals of digitalization was lost from the NAF to the NDUC documents. Finally, a third aim was to investigate if digital tools were implemented in the new NAF Basic Officer's Education, as this would reflect the level of intention of digitalization and specific primary goals of learning and teaching. A mixed methods approach was used in the study as we first investigated documents issued from the government issued for the university and college sector in Norway, the NAF and the NDUC to see if the overall plan for digitalization from the Norwegian Ministry of Education and Research could be traced. In addition, we investigated the answers that officer cadets had given to questions in three course evaluations related to the use of digital tools in their education. Our three hypotheses were the following: Hypothesis 1: Several of the original demands regarding digitalization from the Norwegian government is lost through the dissemination down through the governing documents issued from the ministry to the NAF Basic Officer's Education. Hypothesis 2: No plan has been prepared as part of the educational change process for the introduction and implementation of new digital tools in the NAF Basic Officer Education. Hypothesis 3: It is up to single individuals to introduce and implement the use of new digital tools in the NAF Basic Officer Education. Support for all three hypotheses were received. The article discusses some leadership challenges that are actualized based upon the results we found.